A Broadband Dual-Polarized Magneto-Electric Dipole Antenna Element for Low-Frequency Astronomical Arrays - Murugesan, Akila; Natarajan, Divya; Abishek, S.; Lingasamy, V; K, Hariharan; Selvan, Krishnasamy T. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents simulation-based design and analysis of a broadband dual-polarized magneto-electric dipole antenna element that can be used to construct VHF astronomical antenna arrays. The antenna consists of two pairs of radiating structures, each fed by a Γ-shaped feeding section. The feeding section and radiating parts are physically disconnected from each other. The antenna is evaluated by simulation, and its −10 dB impedance matching bandwidth ranges from 115 to 340 MHz. The maximum gain of the antenna is about 8 dB over the operating range. Isolation of about 20 dB is observed between the two input ports.